Predicting the Gleason sum of a patient with a prostate biopsy core Gleason ≤7 and a prostate biopsy core Gleason ≥8 - Heimrath, Olivier P.; Kos, Zuzana; Belanger, Eric C.; Cagiannos, Ilias; Morash, Chris; Gerridzen, Ronald G.; Lavallee, Luke; Preston, Mark A.; Witiuk, Kelsey; Breau, Rodney H. (Canadian Urological Association Journal, 2014)
Introduction: We review a subset of men who had discordant prostate biopsy sums and were treated with radical prostatectomy. Methods: Consecutive patients treated with radical prostatectomy at The Ottawa Hospital between 2000 and 2012 were reviewed. Those with at least 1 prostate biopsy core of Gleason sum ≥8 and at least 1 prostate biopsy core of Gleason sum ≤7 cancer were included. Results: Of the 764 radical prostatectomies, 661 (87%) were eligible for the study and 35 (5%) met inclusion criteria. Of these, only 16 (46%) had prostatectomy Gleason sum of ≥8. When the highest biopsy core was Gleason sum 8 (n = 24), only 7 (29%) had a prostatectomy Gleason sum ≥8. When the highest biopsy core was Gleason 9 (n = 11), 9 (82%) had a prostatectomy Gleason sum ≥8 (relative risk [RR] 2.8; p = 0.004). Patients with clinical T3 tumours were at higher risk of Gleason sum ≥8 compared to cT1 patients (RR 3.7; p = 0.008). Patient age (p = 0.89), preoperative prostate-specific antigen (p = 0.34), prostate volume (p = 0.86), number of biopsy cores (p = 0.18), and proportion of biopsy cores with cancer (p = 0.96) were not strongly associated with risk of prostatectomy Gleason sum ≥8. Conclusion: These data should be considered when assigning patients into prognostic risk categories based on prostate biopsy information. Further study to verify our findings using larger samples is warranted.